2022
DOI: 10.7717/peerj.14299
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced factor and its role in liver fibrosis

Abstract: Liver fibrosis develops as a result of severe liver damage and is considered a major clinical concern throughout the world. Many factors are crucial for liver fibrosis progression. While advancements have been made to understand this disease, no effective pharmacological drug and treatment strategies have been established that can effectively prevent liver fibrosis or even could halt the fibrotic process. Most of those advances in curing liver fibrosis have been aimed towards mitigating the causes of fibrosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…Our results show a considerable change in the alteration of ECM interactions, which has been linked to the imbalance and impairment of liver function upon treatment with thioacetamide [ 42 , 43 ]. Liver disease progression is known to be related to HIF, PI3K-AKT, and apelin pathways, which are known to participate in different cell activations of inflammation and proliferation [ 44 , 45 , 46 ]. A number of other cellular and miscellaneous pathways also showed consistent down-regulation trends across all the lots after thioacetamide exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Our results show a considerable change in the alteration of ECM interactions, which has been linked to the imbalance and impairment of liver function upon treatment with thioacetamide [ 42 , 43 ]. Liver disease progression is known to be related to HIF, PI3K-AKT, and apelin pathways, which are known to participate in different cell activations of inflammation and proliferation [ 44 , 45 , 46 ]. A number of other cellular and miscellaneous pathways also showed consistent down-regulation trends across all the lots after thioacetamide exposure.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that GLUT1 and HK1/2 are upregulated in keloid fibroblasts, promoting the collagen synthesis and fibrosis development ( Vinaik et al, 2020 ; Wang Q. et al, 2021 ). TGF-β also induces the glycolytic reprogramming by HIF-1 in hepatic stellate cells (HSCs), which plays an important role in increasing collagen production and finally hepatic fibrosis ( Hanna et al, 2013 ; Mohammad Omar et al, 2022 ). Additionally, TGF-β1 upregulates glutaminase (GLS) expression in myofibroblasts, thereby increasing glutaminolysis to provide energy for the synthesis of ECM protein ( Bernard et al, 2018 ).…”
Section: Inflammation-driven Metabolic Reprogramming In Fibrotic Fibr...mentioning
confidence: 99%
“…In Southeast Asia, the main causes of liver cirrhosis are hepatitis B and C. The incidence of liver cirrhosis in Indonesia due to hepatitis B ranges from 21.2-46.9%, and hepatitis C ranges from 38.7-73.9%. 1,2 Currently, there are no pharmacological drugs that are effective in preventing liver fibrosis or can even stop the fibrotic process. Meanwhile, treatment strategies for liver fibrosis are mostly aimed at reducing the causes of fibrosis, including the development of antivirals to inhibit the hepatitis virus.…”
Section: Introductionmentioning
confidence: 99%